Students’ Errors in Solving Science Reasoning-Domain of Trends in International Mathematics and Science Study (TIMSS) (Jurnal Pendidikan IPA Indonesia, 2018)
This research aims to identify the errors of students’ answers in solving the TIMSS cognitive domain of reasoning. This research was a qualitative descriptive research. A total 259 students from four secondary schools located in rural and urban areas in Jember, East Java participated in a paper and pencil test. Error identification was examined by reducing the result of wrong students’ answer and grouping based on error type of general errors. The results showed that the average percentage of total errors from the four schools were contradicting error of 7.3%, disregarding evidence error of 5.2%, misreading error of 45.7%, and opinion-based judgment error of 40.9%. In conclusion, there were four types of general errors made by students in answering TIMMS test item of reasoning domain with misreading and disregarding evidence as the highest and lowest error, respectively.